An adaptable steady state aspen hysys model for the methane fuelled solid oxide fuel cell - Anderson, T.; Vijay, P.; Tade, Moses (2014)
An adaptable model for the methane fed internal reforming SOFC using the in built features of Aspen Hysys is presented in this paper. The model includes the electrochemistry, the diffusion phenomena and the reforming kinetics in detail. Three potential methods for representing the SOFC are investigated out of which the recycled reforming model is found to be capable of providing reasonable results over a wide range of operating conditions. The electrochemical model that gives good agreement with experimental data is also identified. From the simulations, it is concluded that the developed model is reasonably accurate over a wide operating range and can be used for steady state analysis. The computational challenges in the modelling are discussed. The model will be used for system level optimisation studies of the SOFC system especially in conjuncture with gas turbines and steam turbines.